2024
DOI: 10.1128/mbio.02248-23
|View full text |Cite
|
Sign up to set email alerts
|

The impact of orphan histidine kinases and phosphotransfer proteins on the regulation of clostridial sporulation initiation

Iman Mehdizadeh Gohari,
Adrianne N. Edwards,
Shonna M. McBride
et al.

Abstract: Sporulation is an important feature of the clostridial life cycle, facilitating survival of these bacteria in harsh environments, contributing to disease transmission for pathogenic species, and sharing common early steps that are also involved in regulating industrially important solvent production by some non-pathogenic species. Initial genomics studies suggested that Clostridia lack the classical phosphorelay that phosphorylates Spo0A and initiates sporulation in Bacillus , leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 90 publications
(150 reference statements)
0
3
0
Order By: Relevance
“…We found that KipI and KipA do not have major effects on C. difficile sporulation, in contrast to B. subtilis , in which KipI impedes sporulation (Wang et al, 1997). The absence of a sporulation effect by the C. difficile Kip proteins is not completely surprising given the considerable differences in the genetic pathways and factors involved in sporulation initiation between B. subtilis and C. difficile (Edwards et al, 2022; Lee et al, 2022; Mehdizadeh Gohari et al, 2024). In B. subtilis, KipI binds to the sporulation activating kinase, KinA to repress spore formation (Jacques et al, 2011, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that KipI and KipA do not have major effects on C. difficile sporulation, in contrast to B. subtilis , in which KipI impedes sporulation (Wang et al, 1997). The absence of a sporulation effect by the C. difficile Kip proteins is not completely surprising given the considerable differences in the genetic pathways and factors involved in sporulation initiation between B. subtilis and C. difficile (Edwards et al, 2022; Lee et al, 2022; Mehdizadeh Gohari et al, 2024). In B. subtilis, KipI binds to the sporulation activating kinase, KinA to repress spore formation (Jacques et al, 2011, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…C. difficile infections are easily spread and difficult to contain because the spore form of the bacterium is resistant to disinfectants and allows the pathogen to survive nearly indefinitely in a dormant state (Ali et al, 2011;Shen, 2020). Although the structure and general form of C. difficile endospores are similar to other species, the environmental and nutritional conditions that lead to sporulation vary greatly among spore-forming bacteria (Lee et al, 2022;Mehdizadeh Gohari et al, 2024;Shen et al, 2019). While some basic nutritional requirements and regulatory factors are shared among the sporulating Firmicutes, it is not possible to predict the role of a given factor based on the presence of orthologs with a known function in another spore-former (A. N. Edwards et al, 2022Edwards et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The σ B protein has been detected in C. acetobutylicum, and is known to modulate the stress response machinery (e.g., GrpE, DnaK DnaJ) in the microorganisms [96,98]. Additionally, the vegetative sigma factor (σ A ) in Clostridium species regulates the initiation of sporulation during the stationary phase (see [99] for a review on Clostridia sporulation). The sporulation-specific σ E and SpoIIGA genes required for the initiation of sporulation contain the σ A promoter-specific sequence along with 0A boxes consistent with the regulation of transcriptional activation by both σ A and Spo0A [100].…”
Section: The 6s Rna and Tmrna Mediated Regulationmentioning
confidence: 99%